Imperial projections: screening the German colonies (Film Europa: German cinema in an international context) - Fuhrmann, Wolfgang (Film Europa, 2015)
The beginning of filmmaking in the German colonies coincided with colonialism itself coming to a standstill. Scandals and economic stagnation in the colonies demanded a new and positive image of their value for Germany. By promoting business and establishing a new genre within the fast growing film industry, films of the colonies were welcomed by organizations such as the Deutsche Kolonialgesellschaft (German Colonial Society). The films triggered patriotic feelings but also addressed the audience as travelers, explorers, wildlife protectionists, and participants in unique cultural events. This book is the first in-depth analysis of colonial filmmaking in the Wilhelmine Era.